2010
DOI: 10.1016/j.devcel.2009.12.023
|View full text |Cite
|
Sign up to set email alerts
|

BCL6 Canalizes Notch-Dependent Transcription, Excluding Mastermind-like1 from Selected Target Genes during Left-Right Patterning

Abstract: Summary While the Notch signaling pathway is one of the most intensely studied intracellular signaling pathways, the mechanisms by which Notch signaling regulates transcription remain incompletely understood. Here we report that B-cell leukemia/lymphoma 6 (BCL6), a transcriptional repressor, is a Notch-associated factor. BCL6 is necessary to maintain the expression of Pitx2 in the left lateral plate mesoderm during the patterning of left-right asymmetry in Xenopus embryos. For this process, BCL6 forms a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 68 publications
0
65
0
Order By: Relevance
“…Such blockage could result from either the failure to completely displace corepressors from Su(H) or if there are proteins specifically bound to the ac promoter that prevent formation of the Su(H)/NICD/Mam ternary complex. The latter mechanism is similar to a corepression mechanism recently described for the cell-specific regulation of the Notch target gene Pitx2 in Xenopus (37). We previously showed that coactivation by Mam is promoter specific and that Mam does not coactivate the ac promoter, even if an SPS element is present (6).…”
Section: Fig 4 Recruitment Of Su(h)mentioning
confidence: 79%
“…Such blockage could result from either the failure to completely displace corepressors from Su(H) or if there are proteins specifically bound to the ac promoter that prevent formation of the Su(H)/NICD/Mam ternary complex. The latter mechanism is similar to a corepression mechanism recently described for the cell-specific regulation of the Notch target gene Pitx2 in Xenopus (37). We previously showed that coactivation by Mam is promoter specific and that Mam does not coactivate the ac promoter, even if an SPS element is present (6).…”
Section: Fig 4 Recruitment Of Su(h)mentioning
confidence: 79%
“…A considerable number of studies have reported complete absence of nodal, lefty, or pitx2 expression (Field et al, 2011; Oki et al, 2010; Sakano et al, 2010; Gaio et al, 1999; Takeuchi et al, 2007; Zhang et al, 2001; Yan et al, 1999; Tsukui et al, 1999; Collignon et al, 1996; Kramer-Zucker et al, 2005; Krebs et al, 2003; Pennekamp et al, 2002), with some reporting 100% absent expression for all three genes. What does complete absence of gene expression mean?…”
Section: Discussionmentioning
confidence: 99%
“…Like in frog (Hilton et al, 2007;Sakano et al, 2010), BCoR mutations randomize LR asymmetry in human embryos (Ng et al, 2004;Hilton et al, 2007), but this does not occur in mouse (Ye et al, 1997;Yoshida et al, 1999). The loss of brain asymmetry observed in mouse mutants with ciliary dyskinesia (Kawakami et al, 2008) is not observed in human patients (Kennedy et al, 1999;Tanaka et al, 1999;McManus et al, 2004;Afzelius and Stenram, 2006).…”
Section: The Mouse As a Model For Mammalian Asymmetrymentioning
confidence: 94%